Viewpoint The Importance of Reviewing the Code. - Juan A. Añel (Communications of the ACM, 2011)
The article presents a discussion of the use of software in scientific research, arguing that software code used in such research should be specified and reviewed when results are published. This is said to be especially relevant in fields which rely heavily on statistical analysis and data mining. An argument is presented that publishing software specifications should be a requirement for peer-reviewed journals.